hw4 is done
This commit is contained in:
parent
6f07bf149c
commit
25fdd4e598
2 changed files with 68 additions and 2 deletions
|
@ -36,7 +36,7 @@ $$\nabla_X L(X,\lambda) = \begin{bmatrix}(-3-\lambda)x^* + 1\\(1-\lambda)y^* +
|
|||
\begin{bmatrix}x^*\\y^*\\z^*\end{bmatrix} =
|
||||
\begin{bmatrix}\frac1{3+\lambda}\\-\frac1{1-\lambda}\\-\frac{1}{2-\lambda}\end{bmatrix}$$
|
||||
|
||||
Then we have the conditions on the equality constraint:
|
||||
Then we have the complementarity condition:
|
||||
|
||||
$$c(X) = {x^*}^2 + {y^*}^2 + {z^*}^2 - 1 = 0 \Leftrightarrow \|X^*\| = 1$$
|
||||
|
||||
|
@ -141,10 +141,76 @@ Then we have the conditions on the equality constraint:
|
|||
$$Ax - b = 0 \Leftrightarrow \begin{bmatrix}x_1 + x_3\\x_2 + x_3\end{bmatrix} =
|
||||
\begin{bmatrix}3\\0\end{bmatrix}$$
|
||||
|
||||
Then we have the conditions on the equality constraint:
|
||||
Then we have the complementarity condition:
|
||||
|
||||
$$\lambda^T (Ax - b) = 0 \Leftarrow Ax - b = 0 \text{ which is true if the above
|
||||
condition is true.}$$
|
||||
|
||||
Since we have no inequality constraints, we don't need to apply the KKT
|
||||
conditions realated to inequality constraints.
|
||||
|
||||
# Exercise 3
|
||||
|
||||
## Exercise 3.1
|
||||
|
||||
The lagrangian of this problem is the following:
|
||||
|
||||
$$L(x, \lambda) = c^T x - \lambda^T (Ax - b) - s^T x$$
|
||||
|
||||
The KKT conditions are the following:
|
||||
|
||||
1. The partial derivative of the lagrangian w.r.t. $x$ is 0:
|
||||
$$\nabla_x L(x, \lambda) = c - A^T \lambda - s = 0 \Leftrightarrow A^T \lambda
|
||||
+ s = c$$
|
||||
2. Equality constraints hold:
|
||||
$$Ax - b = 0 \Leftrightarrow Ax = b$$
|
||||
3. Inequality constraints hold:
|
||||
$$x \geq 0$$
|
||||
4. The lagrangian multipliers for inequality constraints are non-negative:
|
||||
$$s \geq 0$$
|
||||
5. The complementarity condition holds (here considering only inequality constraints,
|
||||
since the condition trivially holds for equality ones):
|
||||
$$s^T x \geq 0$$
|
||||
|
||||
## Exercise 3.2
|
||||
|
||||
We define the dual problem is the following way:
|
||||
|
||||
$$\max b^T \lambda \;\; \text{ s.t. } \;\; A^T \lambda + s = c \; \text{ and
|
||||
}\; s \geq 0$$
|
||||
|
||||
To convert this maximization problem in a minimization one, we flip the sign of
|
||||
the objective and we find:
|
||||
|
||||
$$\min - b^T \lambda \;\; \text{ s.t. } \;\; A^T \lambda + s = c \; \text{ and
|
||||
}\; s \geq 0$$
|
||||
|
||||
We then compute the Lagrangian of the dual problem:
|
||||
|
||||
$$L(\lambda, x) = -b^T \lambda + x^T (A^T \lambda + s - c) - x^T s = - b^T \lambda + x^T (A^T \lambda - c)$$
|
||||
|
||||
The KKT conditions are the following:
|
||||
|
||||
1. The partial derivative of the lagrangian w.r.t. $x$ is 0:
|
||||
$$\nabla_{\lambda} L(\lambda, x) = - b^T + x^T A^T = 0 \Leftrightarrow Ax = b$$
|
||||
2. Equality constraints hold:
|
||||
$$A^T \lambda + s = c$$
|
||||
3. Inequality constraints hold:
|
||||
$$c - A^T \lambda \geq 0 \Leftrightarrow s \geq 0 \;\;\; \text{ using 2.\ to find
|
||||
that } s = c - A^T \lambda$$
|
||||
4. The lagrangian multipliers for inequality constraints are non-negative:
|
||||
$$x \geq 0$$
|
||||
5. The complementarity condition holds (here considering only inequality constraints,
|
||||
since the condition trivially holds for equality ones):
|
||||
$$x^T s \geq 0 \Leftrightarrow s^T x \geq 0$$
|
||||
|
||||
Then, if we compare the KKT conditions of the primal problem with the ones above
|
||||
we can match them to see that they are identical:
|
||||
|
||||
- 1.\ from the dual is identical to 2.\ from the primal;
|
||||
- 2.\ from the dual is identical to 1.\ from the primal;
|
||||
- 3.\ from the dual is identical to 4.\ from the primal;
|
||||
- 4.\ from the dual is identical to 3.\ from the primal;
|
||||
- 5.\ from the dual is identical to 5.\ from the primal.
|
||||
|
||||
Therefore, the primal and the dual problem are equivalent.
|
||||
|
|
Binary file not shown.
Reference in a new issue